Effect of organisational and individual factors on intrapreneurial behaviour of public university academicians - Islam, Jahirul (2024)
In recent years, academia in Malaysia is striving to move forward towards more innovative and intrapreneurial culture. However, factors affecting intrapreneurial behaviour of academicians working at the public university in the Southern part of Peninsular Malaysia received limited attention in academic research. Hence, this research aims to examine both organisational and individual factors affecting their intrapreneurial behaviour, since it is assumed that both organisational and individual attributes have independent effects on intrapreneurial exposure. Four organisational factors were identified, namely managerial support, flexible organisational structure, favourable organisational culture and recognition of intrapreneurial activity, whereas four other individual factors were identified, namely proactive personality, self-efficacy, need for autonomy and risk-taking propensity. Three underpinning theories namely, human capital theory, resource-based theory and McGregor’s Theory of X and Y have been adopted to support the prospective findings. Primary data was collected from a sample of 250 respondents who are academicians at four universities in the Southern part of Peninsular Malaysia through online survey questionnaire. The study finds that all the organisational factors and individual factors have an effect on intrapreneurial behaviour of academicians. However, while gender acts as moderating variable, all other factors show significant effect on intrapreneurial behaviour except self-efficacy and recognition of intrapreneurial activity. The study has both theoretical implications and practical implications. Academicians are recommended to develop the abovementioned individual factors and university managements are recommended to provide support and reward in favour of intrapreneurship inside the campus.